Influence on Moral Consciousness in the National Cultural Space Factors (Zien Journal of Social Sciences and Humanities, 2022)
This article provides a comprehensive analysis of the role of continuous education, eenvironment, internet, information communications, as well as social environment, family, neighborhood and religion in the formation of national cultural space as factors influencing moral consciousness.